Taxation and Entrepreneurship in a Welfare State - Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2009)
Does tax policy affect the rate of self-employment in a modern welfare state? This question is analyzed empirically based on Swedish data for the entire post-war period. Available tax data indicate that payroll taxes have had a negative influence on the unincorporated rate of self-employment, though the effect is modest. No effects from regular labor income taxation or capital gains taxation are found. The paper improves upon earlier studies in that it tries to separate the effects of different taxes, and uses cointegration techniques. A further extension is that it studies a Scandinavian high-tax welfare state. Earlier time-series studies analyzing self-employment and taxation have with few exceptions been based on data from countries with relatively low tax levels and less comprehensive welfare systems, notably the US and the UK.
Keywords: H20; J23; L26; 330; Entrepreneurship; Self-employment; Taxation; Welfare state; Selbstständige; Entrepreneurship-Ansatz; Steuerpolitik; Sozialstaat; Kointegration; Schweden